Control interno y su impacto en la situación económica y financiera de la Red de Salud de Otuzco, periodo 2021 - Aguilar Salvador, Ana María (2022)
The purpose of this work was to demonstrate the significant and positive impact generated by internal control in the economic and financial situation of the Otuzco Health Network, during the year 2021, for which the present study was based on the foundations of a non-experimental cross-sectional design of descriptive correlational type, for this said research had a census sample size of 135 public servants, in which a questionnaire was applied as an instrument, to know the information of the internal control and through documentary analysis of the financial statements, know the economic and financial situation.It is worth mentioning that the finding found in the present study allowed us to identify that internal control does generate a significant and positive impact on the economic and financial situation of the Otuzco health network, during the year 2021, thanks to the use of the statistical test. of Pearson's correlation coefficient in 0.679 and its high level of significance of 0.00. On the other hand, it is recommended that the Otuzco Health Network Directorate improve the internal control system, disseminating it continuously, in its public servants and in the while becoming aware of its importance, which is for the achievement of the objectives of the institution.